PENERAPAN STRATEGI PAIKEM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 2 PALAPA UNTUK MENCEGAH DISTRAKSI GAWAI: Implementation of PAIKEM Strategy in Islamic Religious Education Learning at SDN 2 Palapa to Prevent Gadgets Distractions - Muhammad Ilham Jaya Kesuma; Ikhtiar Cahya Ajir; Imam Syafe’i; Eti Hadiati; Ratu Vina Rahmatika (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
At SDN 2 Palapa, the use of gadgets in Islamic Religious Education learning was initially intended to support learning activities, but often caused distractions due to free access to social media and online games. To overcome this, the PAIKEM strategy was implemented to increase participation and reduce learning disruptions. This study analyzes the effectiveness of the PAIKEM strategy in Islamic Religious Education learning with a qualitative descriptive approach using the case study method, data collection through observation, interviews, and documentation. Data validity is strengthened by triangulation of sources, techniques, and time. Data analysis was carried out through reduction, presentation, and drawing conclusions. The results of the study indicate that the PAIKEM strategy helps reduce distractions caused by gadgets and improves students' concentration and understanding of Islamic values through audiovisual media, discussions, and worship simulations. However, challenges such as teacher readiness and limited facilities are still faced. This study highlights the importance of the PAIKEM strategy based on Islamic digital literacy and synergy between schools, teachers, and parents in shaping the character of students in the digital era. Di SDN 2 Palapa, penggunaan gawai dalam pembelajaran PAI awalnya bertujuan mendukung kegiatan belajar, tetapi sering menyebabkan distraksi akibat akses bebas ke media sosial dan permainan daring. Untuk mengatasi hal ini, strategi PAIKEM diterapkan guna meningkatkan partisipasi dan mengurangi gangguan belajar. Penelitian ini menganalisis efektivitas strategi PAIKEM dalam pengajaran PAI dengan pendekatan kualitatif deskriptif metode studi kasus, pengumpulan data dengan observasi, wawancara, dan dokumentasi. Keabsahan data diperkuat dengan triangulasi sumber, teknik, dan waktu. Analisis data dilakukan melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi PAIKEM membantu dalam mengurangi distraksi yang ditimbulkan oleh gawai dan meningkatkan konsentrasi dan pemahaman peserta didik terhadap nilai-nilai Islam melalui media audiovisual, diskusi, dan simulasi ibadah. Namun, tantangan seperti kesiapan guru dan keterbatasan fasilitas masih dihadapi. Studi ini menyoroti pentingnya strategi PAIKEM berbasis literasi digital Islami serta sinergi antara sekolah, guru, dan orang tua dalam membentuk karakter peserta didik di era digital. Kata Kunci: Distraksi Gawai; PAIKEM; Pembelajaran Interaktif; Pendidikan Agama Islam; Sekolah Dasar.